Female Song Rate and Structure Predict Reproductive Success in a Socially Monogamous Bird - Brunton, Dianne H.; Roper, Michelle M.; Harmer, Aaron M. T. (Frontiers in Ecology and Evolution, 2016)
Bird song is commonly regarded as a male trait that has evolved through sexual selection. However, recent research has prompted a re-evaluation of this view by demonstrating that female song is an ancestral and phylogenetically widespread trait. Species with female song provide opportunities to study selective pressures and mechanisms specific to females within the wider context of social competition. We investigated the relationship between reproductive success and female song performance in the New Zealand bellbird (Anthornis melanura), a passerine resident year round in New Zealand temperate forests. We monitored breeding behavior and song over three years on Tiritiri Matangi Island. Female bellbirds contributed significantly more towards parental care than males (solely incubating young and provisioning chicks at more than twice the rate of males). Female song rate in the vicinity of the nest was higher than that of males during incubation and chick-rearing stages but similar during early-nesting and post-breeding stages. Using GLMs, we found that female song rates during both incubation and chick-rearing stages strongly predicted the number of fledged chicks. However, male song rate and male and female chick provisioning rates had no effect on fledging success. Two measures of female song complexity (number of syllable types and the number of transitions between different syllable types) were also good predictors of breeding success (GLM on PC scores). In contrast, song duration, the total number of syllables, and the number of ‘stutter’ syllables per song were not correlated with fledging success. It is unclear why male song rate was not associated with reproductive success and we speculate that extra-pair paternity might play a role. While we have previously demonstrated that female bellbird song is important in intrasexual interactions, we clearly demonstrate here that female song predicts reproductive success. These results, with others, highlight the need for a change in how we view the significance of female secondary sexual traits; traits long underestimated due to a focus on male song.